-2+9=14x-3-13x

Simple and best practice solution for -2+9=14x-3-13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+9=14x-3-13x equation:


Simplifying
-2 + 9 = 14x + -3 + -13x

Combine like terms: -2 + 9 = 7
7 = 14x + -3 + -13x

Reorder the terms:
7 = -3 + 14x + -13x

Combine like terms: 14x + -13x = 1x
7 = -3 + 1x

Solving
7 = -3 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + -1x = -3 + 1x + -1x

Combine like terms: 1x + -1x = 0
7 + -1x = -3 + 0
7 + -1x = -3

Add '-7' to each side of the equation.
7 + -7 + -1x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = -3 + -7
-1x = -3 + -7

Combine like terms: -3 + -7 = -10
-1x = -10

Divide each side by '-1'.
x = 10

Simplifying
x = 10

See similar equations:

| -5c+2=-18 | | -5(x+1)-11=21+3 | | 12(x-3)=-3-9 | | -2+5x=-32 | | 3x^3-9x^2+8x-7=2 | | 3(5y-4)=9y | | 6-x=20 | | -117=2(1-6p)-5p | | 5(5c-1)-4=21c+3 | | -(-9x-9y+4)= | | 3.5x=21 | | 4y^2-25x^2=100 | | 144=16t^2 | | 5=p+3 | | .3x+1.8=8 | | 3a-8a= | | 15x-2y=10 | | 5-.5x-3=4 | | 43y=6(7y-2) | | 6y=5(y+3) | | (x-3)(2x+3)=0 | | 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 | | 2x^2+25=25 | | 2x^2-25=25 | | 2z^2+5=167 | | 15x+3y=12 | | 2x+5x+34*6/46=8 | | 2x+5xx=990 |

Equations solver categories